HUBUNGAN STRES KERJA DAN PRESTASI KERJA KARYAWAN PT. ASURANSI SINARMAS JAKARTA PUSAT PADA DIVISI CREDIT CONTROL - Sunarto, Ading (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The purpose of this study is (1) To determine the level of work stress of employees at PT. Asuransi Sinarmas Central Jakarta, (2) To determine the level of employee performance at PT. Asuransi Sinarmas Central Jakarta, (3) To determine the relationship between work stress and employee performance at PT. Asuransi Sinarmas Central Jakarta. The research method used by the writer is descriptive method, while the data processing is quantitative using statistical analysis. The population and sample in this study are employees of PT. Asuransi Sinarmas Central Jakarta Credit Control Division, with a total sample of 65 respondents. Based on the results of the calculation of the correlation between variables (X) Job Stress and Variable (Y) Employee Work Achievement obtained rxy value of 0.60. Conclusion (1) Job stress level for employees of PT. Asuransi Sinarmas Central Jakarta Credit Control Division is quite high (2) The level of work performance at employees of PT. Asuransi Sinarmas Central Jakarta Credit Control Division is quite good (3) Relationship between work stress and work performance at employees of PT. Asuransi Sinarmas Jakarta Pusat Credit Control Division is positively related, with a r value of 0.60 or located at 0.60 to 0.799 which shows the relationship between job stress variables and work performance is strong. Suggestion (1) In an effort to increase employee performance at PT. Asuransi Sinarmas Central Jakarta Credit Control Division, the company should fix the stresses that exist in the company environment by holding two-way communication, taking the time to be able to hear employee complaints through counseling, observing the ability of each individual employee specifically, not taking sides with certain employees fair and wise in solving problems. (2) Improving health services. (3) Establishment of harmonization of work stress relationships between employees as team work